The modulation effects of plant‐derived bioactive ingredients on chronic kidney disease: Focus on the gut–kidney axis. Issue 1 (1st February 2023) - Jian, Shiyan; Yang, Kang; Zhang, Lingna; Zhang, Limeng; Xin, Zhongquan; Wen, Chaoyu; He, Shansong; Deng, Jinping; Deng, Baichuan
Abstract: Chronic kidney disease (CKD) results mainly from diabetes, hypertension, and glomerulonephritis, which can develop into end‐stage renal disease and CKD‐related complications, thereby causing high morbidity and mortality. This progression is correlated with pathogenic alterations in the gut microbiota that generate uremic toxins, mainly including indoxyl sulfate, p ‐cresol sulfate, and trimethylamine‐ N ‐oxide. The uremic toxins directly or indirectly induce CKD through oxidative stress, inflammatory response, and subsequently renal fibrosis. However, ongoing developments in CKD therapy still lack nutritional guidelines and new pharmacotherapies with significant effects. In this review, we discuss the modulatory effects of plant‐derived bioactive ingredients, such as dietary fiber (oligosaccharides and polysaccharides), polyphenols (e.g., curcumin, anthocyanins, catechins, and resveratrol), and peptides, on gut microbiota and CKD particularly from the view of the gut–kidney axis. We believe that a comprehensive understanding of the underlying mechanisms of CKD is necessary to develop new targeted therapy strategies that will benefit the prevention and treatment of CKD. Abstract : Dietary PBI may have the potential to restore the gut‐kidney axis balance, and serves as a promising strategy in alleviating CKD. On the one hand, PBI can directly alleviate CKD through its antioxidant, anti‐inflammatory, and antifibrotic effects and as ROS scavenger. On the other hand, PBI can regulate gut microbiota to reduce uremic toxins and lipopolysaccharide to indirectly alleviate CKD. PBI, plant‐derived bioactive ingredients; ROS, reactive oxygen species; CKD, chronic kidney disease